FORMULATION AND EVALUATION OF MODIFIED ORAL CHRONOTROPIC DRUG DELIVERY SYSTEMS OF TRAMADOL HYDROCHLORIDE FOR RHEUMATOID ARTHRITIS PAIN - PASAM JYOTHIRMAYI; DEVALARAO G; MANDAVA VENKATA BASAVESWARA RAO (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main aim was to develop a modified oral chronotropic system for timed release tramadol hydrochloride (tramadol HCl). Biological rhythms are highly organized for all functions of the human body both in health and in disease. Hence, drug delivery systems were designed to make possible the treatment of illness based on biological rhythms for improving therapeutic efficacy. Materials and Methods: These systems consist of immediate release core tablet of tramadol HCl using different materials such as SSG, crospovidone, pregelatinized starch and then coated with Tamarindus gum, hydroxypropyl methylcellulose (HPMC), and their combination. This coated tablet is enteric coated with Eudragit L 100, Eudragit S100 to produce lag time period of 5 h. Results: Immediate release systems are optimized with formulation F6 containing pregelatinized starch as an immediate release agent, the formulation is coated with Tamarindus gum, HPMC, and their combination. The release retardant behavior of Tamarindus gum was evaluated in compressed coated formulations. This coated tablet is enteric coated with Eudragit L 100, Eudragit S100 to release the drug after the lag time period of 5 h. Conclusion: A modified oral chronotropic system for timed release of tramadol HCl was made possible with the compressed coated tablets CF3 which shows better drug release followed by enteric coating with Es c coat fulfilled our objective of work.